1996
DOI: 10.1007/bf00665636
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of shear-induced crystallization of an impact polypropylene copolymer

Abstract: International audienceThe crystallization kinetics of polypropylene was observed during shear and after shear experiments under isothermal condition. The crystallizations were performed in a plate-plate and a fiber pull-out device. The nucleation density, the crystalline growth and the overall kinetics were measured and compared with data obtained in a similar way but during static experiments. The morphologies are spherulitic and formed from nuclei which seem to be randomly distributed, α-phase spherulites ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 26 publications
3
116
0
Order By: Relevance
“…The increase in X c seen across the weld seam, making it similar to the X c of the surrounding PP-R plate, can be attributed to the shear forces dominating the crystallization behavior along the weld seams. [ 41 ] The weld seams experience both the highest amount of shear and the highest rate of cooling, and in the case of PP-R mechanical abrasion→DSC and μ-FT-IR microscopy are limited to the low spatial resolution in measurements and intricate variations across the weld seams are averaged out. Using Raman microscopy it could be shown that these variations in X c were present in narrow channels along the weld seams and a gradient of ≈18% in the crystallinity could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in X c seen across the weld seam, making it similar to the X c of the surrounding PP-R plate, can be attributed to the shear forces dominating the crystallization behavior along the weld seams. [ 41 ] The weld seams experience both the highest amount of shear and the highest rate of cooling, and in the case of PP-R mechanical abrasion→DSC and μ-FT-IR microscopy are limited to the low spatial resolution in measurements and intricate variations across the weld seams are averaged out. Using Raman microscopy it could be shown that these variations in X c were present in narrow channels along the weld seams and a gradient of ≈18% in the crystallinity could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…There have been lots of reports about shear-induced ␤ form of PP. 41,42 The spatially and temporally varying shear gradient field in the vibration internal mixer could give rise to the increment in possibility of the accidental discrepancy of molecular chain arrangement, which favors polypropylene chains to alter packing mode into the ␤ form unit cell in the subsequent crystallization. The long entangled molecular UHMWPE or its crystals formed also curled the growing polypropylene lamellae inducing more ␤ crystals.…”
Section: Dsc Analysesmentioning
confidence: 99%
“…The mechanical load can be introduced by pulling a fibre through an undercooled melt at a certain temperature T pull . The shear stress generated by fibre pulling produces row nuclei consisting of the !-phase that induce the growth of a cylindritic growth front [13][14][15][16][17][18][19]37]. These row nuclei surround the fibre in a cylindritic fashion thus the growth front is cylindrical and proceeds in the radial direction.…”
Section: The Shear Induced Formation Of the !-Phasementioning
confidence: 99%
“…Increasing concentration of the chain defects in the polymer chain reduces both the spherulitic growthrate and the overall crystallization rate. Sanchez and Eby [23] derived a general expression for the spherulitic growth rate G (assuming a coherent surface nucleus and regime III growth) (see Equation (18)): (18) It is possible to express the nucleation rate of the copolymer in terms of the homo-polymer nucleation rate plus a term that contains the comonomer concentration if the following function is defined (Equation (19)): (19) The term /G 0 is the bulk free energy difference for the complete defect-free (homo) polymer with infinite lamellar thickness and molar mass compared to the defect containing 'real' lamella of finite thickness and is usually approximated by Equation (20): (20) For /G 0 it is assumed that at moderate undercooling the heat of fusion (/H 0 ) and entropy of fusion (/S 0 ) are temperature independent [45]. From the nucleation theory [45] follows Equation (21): (21) where l c,i is the initial crystal thickness and " e is the surface free energy.…”
Section: Crystallization Of Copolymersmentioning
confidence: 99%
See 1 more Smart Citation